HUBUNGAN ANTARA POLA ASUH DEMOKRATIS DAN KECERDASAN EMOSI DENGAN PERSAINGAN ANTAR SAUDARA - Alif Muarifah; Intan Puspitasari (Departemen Psikologi Universitas Pendidikan Indonesia, 2018)
This research aimed to know the correlation between democratic parenting style and emotional intelligence with sibling rivalry. Sibling rivalry triggered by individual internal or external factors. In this research, democratic parenting style serve as individual external factor and emotional intelligence serve as individual internal factor for sibling rivalry. Participants in this study were selected by purposive sampling technique which are parents who have children in age of 7 to 8 years old. Quntitative method was used by distributing Democratic Parenting Style Scale, Emotional Intelligence Scale and Persaingan antar saudara Scale to the participants. Regression was used to understand the correlation between variables and its correlational strength. This research showed that there is significant negative correlation between democratic parenting style and emotional intelligence with sibling rivalry. Partially, democratic parenting style and sibling rivalry results correlation coefficient r -0.196 meanwhile emotional intelligence and sibling rivalry results correlation coefficient r -0.293. Regression analysis between variables shows R square (R2) valued of 0.88. This result shows that democratic parenting style and emotionl intelligence can explain the variable variances of sibling rivalry valued of 8.8 percent together.